The working woman - Maelzer, Louisa Mary (My University, 1899)
Introduction: The subject of woman is one that has been treated from every point of view, every phase of life now common to woman, and every sphere which it is ever hoped will be attained by her; and yet we feel the importance of his subject so great and pressing that it is worth the deepest interest, sincerity and hope to gain a deeper insight into this question that it is again taken up. It is important, because upon this rests so many other difficulties in our social world. If woman’s place, work and wages, and the condition of woman as a whole be solved, it would without further effort put to flight the any troubles and sorrows which now reign supreme especially in our large cities, among the poorer class of people. A Bit of History. We find that in very early times woman was honored not according to the social ideas of the world, but more according to her character.
Citation: Maelzer, Louisa Mary. The working woman. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Present Status of Woman; Woman's Suffrage; Work and Wages; Theses; Manuscripts (documents)